Effect of temperature variation on hormonal concentration at various gestation stages in black Bengal goat - Binod Kumar; Ajay Kumar Ishwar; Pankaj Kumar Choudhary; Tanveer Akhatar (Veterinary World, 2015)
Aim: The present study was conducted to evaluate the effect of risingtemperature on the metabolic as well as the reproductive performance of the black Bengal goat. Materials and Methods: A total 27 numbers of non-pregnant black Bengal goats of the same parity comprised the experimental animals. The selected goats were randomly assigned to 3 groups of 9 each, maintaining uniformity in body weight (average 14-18 kg). Goats in Group-I were kept between the temperature ranges of 35-40°C, in Group-II between 20°Cand 27°C, and Group-III were kept under loose housing system and serve as a control. Goats in all the groups were bred naturally. Blood was collected prior to feeding in the morning on the day 1 (estrus), 20, 45, 90, and 135, expected day of parturition and also 2 days after parturition from goats of all the three groups. Results: It was observed that the level of plasma estrogen decreased (p˂0.05) up to day 45 of gestation, then after increased up to 135 days of gestation and was maximum on expected day of parturition which was significantly (p˂0.05) higher than all the values. Plasma progesterone level increased from day 20 and was the highest on day 90 and then decreased significantly (p˂0.05) on expected date of parturition. The luteinizing hormone value decreased significantly (p˂0.05) on expected day of parturition and day 2 after parturition in all the groups. Follicle stimulating hormone concentration showed a significant (p˂0.05) decrease from day 1 to 2 days after parturition in all the groups. The plasma triiodothyronine (T3) level did not vary between and within the treatment groups at any stage of the experiment. The plasma thyroxine (T4) level varied significantly (p˂0.01) within and (p˂0.05) between groups at all stages of reproduction. A significant (p<0.05) variation in plasma cortisol concentration in all the groups increased significantly until the day of parturition and dropped significantly (p<0.01) in 2 days after parturition in all the groups. Conclusion: The present experiment revealed that rise in temperature has no any deleterious effect on the metabolic as well as the reproductive hormonal concentrationat variousstages of gestation inblack Bengal goat.